Maternal Obesity-Associated Neonatal Morbidities in Early Newborn Period - Kureshi, Azima; Khalak, Rubia; Gifford, Jamie; Munshi, Upender (Frontiers in Pediatrics, 2022)
Abstract Maternal obesity has been associated with pregnancy related complications and neonatal morbidities. The primary aim of this study was to evaluate early neonatal morbidities associated with maternal obesity from the infant-mother dyad data set at a single large Regional Perinatal Center (RPC) in NY. Retrospective chart review of all mother-infant dyads born from Jan. 2009 to Dec. 2019 was done. Maternal obesity was defined using NIH definition of pre-pregnancy body mass index (BMI) ≥30 Kg/m2. Maternal data included pre-pregnancy BMI, gestational diabetes, hypertension, and mode of delivery. Neonatal data recorded the birth weight, gestational age, respiratory support after delivery room, diagnosis of transient tachypnea of newborn (TTN), respiratory distress syndrome (RDS), neonatal hypoglycemia (NH), and hypoxic ischemic encephalopathy (HIE). Diagnosis of TTN, RDS, NH, and HIE were defined by the service neonatologist and cross checked by data system review neonatologist. Medical records of 22,198 infant- mother dyads included in the study had 7,200 infants (32.4%) born to obese mothers and 14,998 infants (67.6%) born to non-obese women. There was a statistically significant increase in diagnosis of gestational diabetes, gestational hypertension, and cesarean deliveries in obese mothers. Diagnosis of TTN, RDS, and NH were significantly higher in infants born to obese mothers while HIE incidence was similar in both the groups. Infants born to obese mothers are more likely to be delivered by cesarean section, and are at a higher risk of diagnosis of transient tachypnea of newborn, respiratory distress syndrome, and hypoglycemia in the early neonatal period